Rio de Janeiro aquém de 2016: A oportunidade adiada para despoluiç\~ao do complexo de rios, de lagoas e da Baía de Guanabara - Rosane S. Lourenço (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This study, which belongs to the series new generation of infrastructure, reflects the major advances of information technology, biotechnology and nanotechnology in the development of sanitation and water resources sectors. International and notorious cases have been catalogued in compared studies with the case of southeastern Brazil, the State and the city of Rio de Janeiro. The research made it possible to identify conceptual models of ecological sanitation that approximate human actions to natural systems. The evaluation was extended to management mechanisms for water production, sewerage, drainage and solid waste systems, in anticipation of the need for addressing future challenges, such as extreme events and climate change. Finally, propositions are designed along the study, urging reflection on the range of possible choices.
Keywords: L95; 330; sustainable infrastructure; sanitation models; water resources; Rio